Bats ecology in the Dry Tropical Forest of Nariño (Colombia) and some commentaries about their conservation - Cabrera-Ojeda, Christian (2016)
Tropical dry forests are considered as threatened ecosystems in Colombia, because they are located in areas with intensive human activities. However, the effects of habitat loss on the distribution and abundance of bats in this region are little known. The purpose of this study was to analyze species richness, composition and relative abundance of bats in three vegetation types with different degrees of intervention in the Tropical Dry Forest of Nariño (Mesi: Intervened dry thorn scrub, Mesc: Preserve dry thorn scrub, Bsi: Intervened semideciduous tropical forest), Colombia. We captured bats using 10 mist nets over 24 nights (eight nights in each vegetation type). Nine species were recorded from the capture of 60 specimens. The Mesc had the higher richness (6 species), while the Mesi had the lower richness (4 species). This is probably related with the high degree of human disturbance in the area. Sorensen index (0.33-0.38) indicated that the three populations represent the same community. A. lituratus (Dtsi), A. planirostris (Tsfi) and C. perspicillata (Dtsp) showed the lower abundance, this condition has been associated with forest in process of regeneration or forest with human intervention. Although the best preserved area is the Mesc, criteria as the low species richness, dominance of the three bat species and the presence of Desmodus rotundus suggest that the degree of human intervention is similar in the three types of vegetation. Therefore it is necessary to establish bat conservation programs and restoration projects in the area.